Faktor-Faktor Yang Mempengaruhi Produksi Usahatani Kopi Di Kecamatan Rangsang Pesisir Kabupaten Kepulauan Meranti - Ryan E Syahrial; Fajar Restuhadi; Jumatri yusri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This research aims to determine and analyze the factors that affect the production of coffee in RangsangPesisirSub District. This research uses survey method to conduct interview with 75 sample of coffee farmers obtained by using the slovin method with field trips to their farms. Factors affecting agricultural production are analyzed using the Cobb Douglass production function and using the least estimated squares method. There are four factors of coffee production are assessed influen : number of coffee crops, amount of manure, pesticides, and labor. The variable significantly affect coffee production in RangsangPesisirSub District is the number of coffe crops and labor. Keyword : coffee, production factor, cobbdouglas, rangsang pesisir